Brain volumes and white matter microstructure in 8- to 10-year-old children born with fetal growth restriction - Korkalainen Noora; Ilvesmäki Tero; Parkkola Riitta; Perhomaa Marja; Mäkikallio Kaarin (SPRINGER, 2022)
Background Fetal growth restriction caused by placental insufficiency is associated with increased risk of poor neurodevelopment, even in the absence of specific perinatal brain injury. Placental insufficiency leads to chronic hypoxaemia that may alter cerebral tissue organisation and maturation.
Objective The aim of this study was to assess the effects fetal growth restriction and fetal haemodynamic abnormalities have on brain volumes and white matter microstructure at early school age.
Materials and methods This study examined 32 children born with fetal growth restriction at 24 to 40 gestational weeks, and 27 gestational age-matched children, who were appropriate for gestational age. All children underwent magnetic resonance imaging (MRI) at the age of 8-10 years. Cerebral volumes were analysed, and tract-based spatial statistics and atlas-based analysis of white matter were performed on 17 children born with fetal growth restriction and 14 children with birth weight appropriate for gestational age.
Results Children born with fetal growth restriction demonstrated smaller total intracranial volumes compared to children with normal fetal growth, whereas no significant differences in grey or white matter volumes were detected. On atlas-based analysis of white matter, children born with fetal growth restriction demonstrated higher mean and radial diffusivity values in large white matter tracts when compared to children with normal fetal growth.
Conclusion Children ages 8-10 years old born with fetal growth restriction demonstrated significant changes in white matter microstructure compared to children who were appropriate for gestational age, even though no differences in grey and white matter volumes were detected. Poor fetal growth may impact white matter maturation and lead to neurodevelopmental impairment later in life.